Phenotypic Evaluation of Fe and Zn Content and Agronomic Traits in Sorghum Segregating Population - Mufidah Mufidah; Desta Wirnas; Trikoesoemaningtyas Trikoesoemaningtyas; Reflinur Reflinur (Department of Agronomy and Horticulture, IPB University, 2026)
Biofortification is one approach to overcoming micronutrient deficiencies by enhancing the nutritional content of food crops. Biofortification of sorghum’s iron (Fe) and zinc (Zn) content is essential to increase sorghum’s value as an alternative carbohydrate source. This research aimed to study phenotypic variation in Fe and Zn content and its correlation with agronomic traits and yields in the F3 population generated from a cross between the ‘Demak 4’ and ‘Soper 6 Agritan’ developed using the Single Seed Descent (SSD) method. This research was conducted at the Muara Experimental Field in Bogor, from May to August 2024. The experiment used an augmented design with four replications based on an individual-based segregated design. Fe and Zn content in sorghum grain samples was measured using an X-ray fluorescence machine. The results showed that the Fe content in sorghum grain within the F3 population ranged from 11.70-21.80 ppm, and Zn content ranged from 16.70-26.25 ppm. The correlation analysis showed that Fe content was not related to agronomic traits or yield. Zn showed a significant positive correlation with flag leaf area (r = 0.30, p < 0.01) and stem diameter (r = 0.24, p < 0.05). Fe and Zn content of sorghum grain was observed to be positively correlated (r = 0.68, p < 0.001). The results of multi-character identification using MGIDI yielded 10 selected genotypes: G1, G2, G6, G18, G20, G63, G82, G108, G122, and G181. Genotypes G1, G2, G181, and G122 are suitable for high yield.